Transformation open and distance learning (ODL) for studio based architectural design courses / Abdul Hadi Nawawi ... [et al.] - Nawawi, Abdul Hadi; Rosman, Siti Hasniza; Ismail, Suhana; Nik Azhari, Nik Farhanah (UiTM Press, 2024)
Transitioning studio-based architectural design courses to an Open and Distance Learning (ODL) format requires careful planning and creative solutions to maintain the quality of the learning experience among university students. At ODL, it trying to re-design the programs and their implementation to suit with learners’ actual needs. This paper examines transformation Open and Distance Learning (ODL) for Studio-Based Architectural Design Courses. The research findings support the use of Synchronous (Physical Design Studio) and Asynchronous (Virtual Design Studio) platforms to teach studio-based architectural design courses a constructive learning journey from start to end. ODL made available at a distance, adopting the traditional expression of distance learning into new technological situations.